A suicide bereavement model: based on a meta-ethnography of the experiences of adult suicide loss survivors - Whitebrook, John; Lafarge, Caroline; Churchyard, Jamie S. (Frontiers in Public Health, 2025)
IntroductionThe annual suicide death rate is c.760,000 therefore, using the widely accepted estimate of 135 people being exposed to each suicide, the worldwide annual exposure rate is over 100 million. While male suicide-loss survivors (SLSs) are equally exposed, the vast majority of suicide bereavement research includes a large majority of female participants.MethodsFollowing the eMERGe and PRISMA guidelines, a meta-ethnography (systematic review of qualitative studies) was carried out to assess historical research into suicide-loss survivorship. Seven data sources were searched, up to 30-Nov-2022, for peer-reviewed studies, written in English, that used identifiable and interpretative qualitative methods, had at least 50% male participation, and offered a valuable contribution to the synthesis.ResultsOverall, 1,645 records were screened, and 15 reports of included studies assessed. Eight main themes were identified: changed forever, trauma, stigmatization, protector, lost futures, lost in plain sight, societal norms, and dualities. Via line of argument synthesis, and considering the broader literature, a model for suicide bereavement, applicable to all, is proposed that brings together the gamut of pertinent factors into an integrated framework.DiscussionThe model could be used in practice (clinical, therapy/counseling, education) to enable better understanding of the highly complex and interwoven components of suicide bereavement, thereby facilitating improved and extended services available to SLSs that are more in-tune with their needs. While the model cannot confer full comprehension of suicide bereavement, it can go a long way to assist those looking to assist SLSs by providing a platform for dialogue and empathy.